The complete mitochondrial genome of Congjiang miniature pig (Sus scrofa). (3rd May 2016) - Ran, Mao-Liang; Wang, Ming-fu; Yang, An-Qi; Li, Zhi; Chen, Bin
Abstract: Congjiang miniature pig is one of the most important local pig breeds in China. It is the first time that the complete mitochondrial genome sequence of Lantang pig is reported in this work, which is determined through the PCR-based method. The total length of the mitogenome is 16, 772 bp, which contains 1 control region (D-loop region), 2 ribosomal RNA genes, 13 PCGs and 22 tRNA genes. The total base composition of Congjiang miniature pig mitochondrial genome is 34.78% for A, 26.21% for C, 25.78% for T and 13.22% for G and in the order A>C>T>G. The complete mitochondrial genome of Congjiang miniature pig provides an important data in genetic mechanism and the evolution genomes.